Skinner’s Presence in References on Brazilian Digital Behavior Analysis Journals (Brazilian Journal of Behavioral and Cognitive Therapy, 2020)
Skinner's work has been the subject of many historical investigations, including analysis of citations to his works. Such studies allow for evaluating the impact of particular literary works. This research aimed to identify references to Skinner in behavior analysis articles published on Brazilian digital behavior analysis journals. All original behavior analysis articles published until 2019 on Brazilian behavioral-analytical journals were analyzed. A total of 728 articles were analyzed, and 22,090 references were identified, being 1,577 (7.1%) of them to Skinner. Most of those works made no-or just one-citation to Skinner, and most of Skinner's publications were not cited in the articles analyzed. Such data indicate the need to expand access to different Skinner's works to reach a better understanding of his work and theory.
Keywords: behavior analysis; bibliometric analysis; B. F. Skinner; history of psychology; scientometry